Aspek Pendidikan Akhlak dalam Film Animasi Riko The Series - Surnita Surnita; Syafei Syafei (An-Nuha, 2022)
This study aims to find out what aspects of akhlak education are contained in the animated film "Riko The Series" by Teuku Wisnu, Arie Untung, and Yuda Wirafianto. This type of research is a maximum of qualitative research with research subjects that are directly from the animated film "Riko The Series" season two starting from episodes 1-21. The data was obtained using documentation and observation techniques. From the results of the study, it was found that aspects of akhlak education in the animated film Riko The Series season two include: 1) Aspects of akhlak education to Allah, namely being grateful, serving Allah, loving and fearing Allah, tawakal and istigfar. 2) Aspects of akhlak education among human beings, namely to oneself which consists of being patient and forgiving. 3) Aspects of akhlak education to parents. 4) Aspects of akhlak education for brothers. 5) Aspects of akhlak education towards friends. 6) Aspects of akhlak education on the environment.